Study the Effect of Blade Angles on the Performance of Axial Six Blades Wind Turbine - A AbdulKareem, Mishaal; A Hussain, Ammar; S Fahad, Raid (International Journal of Engineering and Technology, 2018)
In this paper, the performance of a six blades axial type wind turbine has been studied experimentally to estimate the wind power, the electrical generated power and-the modified power-coefficient of the wind-turbine. This study was conducted under different operating conditions assuming steady-state, incompressible and isothermal air flow through the wind-turbine. The range of operating condition was (2 to 5.6 m/s wind speed), (10% to 100% of electrical load that is applied on the terminals of the electrical generator) and (10° to 80° blades angle of the wind-turbine). A good agreement was obtained when comparing the results of the present work with those of a previously published article. The predicted results showed that increasing the wind speed and-the blades angle of the wind-turbine will increase the generated power from the wind-turbine. The maximum-value of the modified power-coefficient was (0.57) at a wind velocity value of (5.6 m/s) and at a blades angle value of (80°). It is found that it’s not recommended to operate the wind-turbine at (80°) blades angle associated with a wind speed range that is above (3.8 m/s) due to a high level of wind-turbine vibration.